HOW RECOGNIZING THE ENDOGENEITY OF IDENTITY RENDERS THE DISCOUNTING DEBATE LARGELY IRRELEVANT (Utah Environmental Law Review, 2010)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Many social policies require the substantial commitment of resources in order to provide benefits for future generations. Conventional policy assessment by the usual willingness to pay valuation criterion raises the issues of whether the future benefits of a policy should first be discounted to a smaller present value before comparison with its current costs in order to assess its merits, and if so then what discount rate should be utilized for these calculations. There is, however, less at stake in this debate than the partisans on either side commonly realize. This is because of the failure of policy analysts to recognize that all policies have pervasive and eventually universal and eternal "person-altering consequences" for genetic identities, the nature of which is explained in this Article. These consequences, if measured by estimated willingness to pay, will provide truly massive benefits for future generations, but they are not amenable to meaningful quantification. Therefore, these discounting issues do not arise with regard to these kinds of consequences. Moreover, because the largest proportion by far of the persons who will be impacted by a policy will be affected in a person-altering manner, the resolution of these discounting issues with regard to valuing the future impacts of a policy on existing persons is of limited practical importance.